Bacterial quorum sensing and the role of algae in bacterial diseases control in aquaculture - . Wiyoto; Julie Ekasari (Jurnal Akuakultur Indonesia)
Bacterial disease is one of the most common diseases in aquaculture practices which have a significant impact. Several researches noted that pathogenicity of a certain bacteria can be determined by its quorum sensing activity. Quorum sensing is a communication process of a certain bacteria with the same or different species of bacteria which involves the releasing and capturing of signal molecule to and from the environment. This activity will activate a certain target gene which further resulted in the expression of a phenotype by the bacteria. With regard to this characteristic, one of the methods to control bacterial diseases is by quorum sensing disruption. Several species of algae, both micro and macro, have been found to be able to intervense bacterial quorum sensing and thus can be used as an alternative in bacterial disease control.